Mono and dinuclear complexes of half-sandwich platinum group metals (Ru, Rh and Ir) bearing a flexible pyridyl-thiazole multidentate donor ligand - Prasad, Kota Thirumala; Therrien, Bruno; Rao, Kollipara Mohan (My University, 2009)
The mononuclear cationic complexes [(?6-C6H6)RuCl(L)]+ (1, L = 2,2'-bis(2-pyridyl)-4,4'-bithiazole), [(?6-p-iPrC6H4Me)RuCl(L)]+ (2), [(?5-C5H5)Ru(PPh3)(L)]+ (3), [(?5-C5Me5)Ru(PPh3)(L)]+ (4), [(?5-C5Me5)RhCl(L)]+ (5), [(?5-C5Me5)IrCl(L)]+ (6) as well as the dinuclear dicationic complexes [{(?6-C6H6)RuCl}2(L)]2+ (7), [{(?6-p-iPrC6H4Me)RuCl}2(L)]2+ (8), [{(?5-C5H5)Ru(PPh3)}2(L)]2+ (9), [{(?5-C5Me5)Ru(PPh3)}2(L)]2+ (10), [{(?5-C5Me5)RhCl}2(L)]2+ (11) and [{(?5-C5Me5)IrCl}2(L)]2+ (12) were synthesized from 2,2'-bis(2-pyridyl)-4,4'-bithiazole (L) and the corresponding complexes [(?6-C6H6)Ru(?-Cl)Cl]2, [(?6-p-iPrC6H4Me)Ru(?-Cl)Cl]2, [(?5-C5H5)Ru(PPh3)2Cl], [(?5-C5Me5)Ru(PPh3)2Cl], [(?5-C5Me5)Rh(?-Cl)Cl]2 and [(?5-C5Me5)Ir(?-Cl)Cl]2, resp. All complexes were isolated as hexafluorophosphate salts and characterized by IR, NMR, mass spectrometry and UV-visible spectroscopy. The x-ray crystal structure analyses of [3]PF6, [5]PF6, [8](PF6)2 and [12](PF6)2 reveal a typical piano-stool geometry around the metal centers with a five-membered metallo-cycle in which 2,2'-bis(2-pyridyl)-4,4'-bithiazole acts as a N,N'-chelating ligand. [on SciFinder(R)]
Keywords: dinuclear pyridylthiazole platinum group half sandwich prepn structure UV; pyridylthiazole reaction chloro benzene cyclopentadienyl phosphino ruthenium rhodium iridium; crystal structure pyridylthiazole ruthenium rhodium iridium half sandwich prepn; mol structure pyridylthiazole ruthenium rhodium iridium half sandwich prepn